2007
DOI: 10.1097/01.pas.0000213343.55605.b9
|View full text |Cite
|
Sign up to set email alerts
|

HLA-A, -B, -C Expression in Colon Carcinoma Mimics That of the Normal Colonic Mucosa and is Prognostically Relevant

Abstract: Whether human leukocyte antigen (HLA)-A, -B, -C expression has any predictive value on the prognosis of human malignancies remains controversial. Herein, monoclonal antibodies with preferential reactivity for HLA-A, HLA-B, and HLA-C (HCA2, HC10, and L31) were used to stain an archival collection of 291 formalin-fixed/paraffin-embedded tissues, comprising neoplastic lesions from stages II and III colon carcinoma patients (n=165), and the uninvolved, morphologically normal mucosae from a subset (n=126) of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 29 publications
3
20
0
1
Order By: Relevance
“…Accordingly, several immunohistochemical studies failed to confirm an association between HLA-A, -B, - C loss and poor prognosis [10-12], and our own studies were consistent with activation-inhibition models [13-16]. We showed that early-passage melanoma, breast carcinoma, and lung carcinoma cells, like virus-infected cells, avoid both extremes of overly low or high HLA class I expression, which would expose them to lysis by NK and CTLs, respectively.…”
Section: Introductionsupporting
confidence: 82%
“…Accordingly, several immunohistochemical studies failed to confirm an association between HLA-A, -B, - C loss and poor prognosis [10-12], and our own studies were consistent with activation-inhibition models [13-16]. We showed that early-passage melanoma, breast carcinoma, and lung carcinoma cells, like virus-infected cells, avoid both extremes of overly low or high HLA class I expression, which would expose them to lysis by NK and CTLs, respectively.…”
Section: Introductionsupporting
confidence: 82%
“…When HC10 in isolation with b2-m was studied, reduced expression of HLA class 1 was predictive of poor outcome. The observation by Benevolo et al (2007) and Menon et al (2002) that HC10 expression alone was not associated with outcome further supports the importance of b2-m in antigen representation.…”
Section: Discussionsupporting
confidence: 64%
“…It is not yet known when these antigens appear in the adrenal cortex, but they are probably involved in cellular differentiation. Loss of expression of HLA class antigens or deregulation has been reported in a great variety of tumors, including breast, cervix, larynx, colon, and pancreas cancers [26][27][28][29][30][31][32]. In a study of gene expression by microarray analysis, carried out on 24 pediatric ACTs (5 adenomas, 18 carcinomas, 1 tumor classified as indeterminate for malignancy), West et al [12] identified 52 probe sets for which significant differences were found when comparing adrenocortical adenomas versus carcinomas.…”
Section: Discussionmentioning
confidence: 99%